Antibacterial Activity of N-Hexan and Ethyl Asetet Fraction of Ethanol Extract of Red Atai (Plagiogyria pycnophylla (Kunze) Mett.) Leaves on Propionibacterium acnes Bacteria - Reksi Sundu; Nurul Fatimah; Andi Mismawati (Journal Prima Health Science, 2019)
Ferns are cormophyte plants with spore, which can live anywhere.The number of ferns and their spread is high, especially in tropicalrain areas. The purpose of this study was to determine theantibacterial activity of the n-hexane and ethyl acetate fraction ofethanol extract of the red atai fern (Plagiogyria pycnophylla (Kunze)Mett.) leaves against Propionibacterium acnes bacteria. The stages ofthe study were sample collection, extraction, fractionation,phytochemical screening and antibacterial activity testing using theKirby-Bauer disc diffusion method. The results showed that the nhexanefraction each of 2,5%; 5%; 10% and 20% concentrations hada medium category with successive inhibition zone diameter values of7,20 mm ± 0,60; 7,55 mm ± 0,07; 7,56 mm ± 0,48 and 7,73 mm ±0,88. The ethyl acetate fraction at a concentration of 2.5%, 5% and10% had medium category inhibition with diameter of inhibitionzones respectively 7,97 mm ± 0,81; 8,55 mm ± 0,49 and 9,12 mm ±0,35, while at a concentration of 20% have strong category (13,73mm ± 0,75). From the results of the above study, it can be concludedthat the n-hexane and ethyl acetate fraction of the ethanol extract ofthe red atai fern (Plagiogyria pycnophylla (Kunze) Mett.) leaves haveantibacterial activity against Propionibacterium acnes.